The Internet: A black hole releasing new stars. Business models and regulation - Pier Luigi Parcu; Maria Luisa Stasi (International Telecommunications Society (ITS), 2014)
The Internet ecosystem is rapidly and constantly expanding. In numerous sectors, the Internet has acted as a 'black hole', attracting the majority of transactions and leaving less and less space to the offline businesses. Among others, the Internet has dematerialized physical assets and services, lowered down of the production and distribution costs, strongly contributed to the diffusion of the 'free' goods and services, multiplied the multi-sided markets and caused a shift from supply-driven systems toward demand-drive ones. All these features have impacted the traditional ways of performing economic activities. In order to cope with the disruptive effect of the Internet, firms have transferred their business online, adapted and evolved their business models or created completely new ones. Often, the outcome of such transformations creates frictions with the traditional regulatory environment where the businesses take place, and decision-makers and enforcers must deal with unprecedented challenges. In order to efficiently regulate the online markets, decision makers and regulators might need to undergo the same process that firms were called to perform: transfer and adapt the rules to the online world. While accomplishing this change, it might also be that, in some cases, it will be more efficient to set completely new rules instead of trying to stretch the old tools to newly created online businesses.
Keywords: 330